Blockchain Application On Independent Smart Agriculture - Hilabi, Shofa Shofiah; Fauzi, Ahmad; Tukino, Tukino (International Journal of Artificial Intelligence Research, 2023)
The agricultural supply chain is currently facing challenges such as lack of transparency, uncertainty in product origin, and difficulty in accurately tracking products. This article discusses the application of blockchain technology as a solution to enhance agricultural supply chain management. It analyzes how blockchain can improve transparency, reliability, and security in agricultural supply chain management by recording and verifying information in a decentralized manner. Through blockchain, information such as product origin, production methods, shipping details, and storage conditions can be easily traced and verified by the involved parties. The implementation of blockchain also enables smart contracts to automatically execute agreements and payments based on predefined conditions, reducing bureaucracy and enhancing efficiency. The article also addresses challenges in implementing blockchain in the agricultural supply chain, such as data standardization and collaboration among stakeholders. By implementing blockchain technology, it is expected to create a more transparent, efficient, and trusted agricultural supply chain, benefiting farmers, producers, distributors, and consumers by ensuring product authenticity, improving compliance with quality standards, and minimizing the risks of counterfeiting or contamination.Â Â